Embedded software development for safety-critical systems - Hobbs, Chris (CRC Press, 2016)
"Embedded Software Development for Safety-Critical Systems discusses the development of safety-critical systems under the following standards: IEC 61508, ISO 26262, EN 50128, and IEC 62304. It details the advantages and disadvantages of many architectural and design practices recommended in the standards, ranging from replication and diversification through anomaly detection to the so-called "safety bag" systems."--Back cover
"An Auerbach book."
Keywords: Computer software -- Development.; Embedded computer systems.; System safety.; Computer security.; Automatic control -- Reliability.; Software engineering.; elektronické knihy; electronic books